A Diels–Alder/Ene Cascade Leading to 5‐(Pyrrolidin‐3‐yl)thieno[3, 2‐e]isoindoles from Ketone‐derived 2‐Vinylthiophenes and N‐Phenylmaleimide. (31st October 2018) - Noland, Wayland E.; Huisenga, Matthew P.; Herzig, Ryan J.; Rosenow, John A.; Kim, Hoyeon; Kroll, Neil J.; Nesmelov, Andrei; Johnson, Benjamin T.; Duncan, Nathan S.; Ratanayanon, Jidapa; Yue, Ruixian A.; Xiong, Kenny; et al.
Abstract : In an extension of our prior work with indoles and pyrroles, the Diels–Alder chemistry of substituted 2‐vinylthiophenes was explored, using N ‐phenylmaleimide as the dienophile. The dienes were prepared from thiophene in two steps by addition to various ketones, followed by dehydration (40–60% overall yields). Although most dienes were obtained as regioisomeric mixtures, the Diels–Alder‐derived products were easily purified by chromatography. The main cycloaddition pathway was endo Diels–Alder addition followed by exo ene addition of a second molecule of dienophile (19–33% yields). Several products were desulfurized with Raney nickel (48–62% yields). Unfortunately, no thiophene‐derived products showed the promising biological activity of the previously reported indole analogs. Abstract :